Nanostructured Antimony/carbon Composite Fibers as Anode Material for Lithium-ion Battery. (1st January 2015) - Lv, Hailong; Qiu, Song; Lu, Guixia; Fu, Ya; Li, Xiaoyu; Hu, Chenxi; Liu, Jiurong
Abstract: Antimony/carbon (Sb/C) composite fibers with Sb nanoparticles uniformly dispersed in carbon matrix have been successfully fabricated by a facile spinning approach and the subsequent calcination in argon flux. As the anode materials of lithium-ion battery, experimental results reveal that the increase of Sb concentration enhanced the lithium-ion storage capacity and worsened the cycling performance. Carbon matrix could efficiently buffer the volume change and maintain the integrity of electrode during the lithiation/delithiation, improving the cycling capability. Among the Sb/C composite fibers, the sample (Sb5) with appropriate carbon content of ca. 50.1 wt% achieves a reversible capacity of 315.9 mAh g −1 after 100 cycles at a current density of 100 mA g −1 and the capacities of 464.4, 395.4, 328, 246.2 and 149.8 mAh g −1 at 100, 200, 400, 800 and 1600 mA g −1, respectively. Electrochemical impedance spectroscopy (EIS) results indicate that Sb5 shows more superior charge transfer rate and Li-ion diffusion ability than the samples with high Sb concentration (Sb6) or carbon concentration (Sb4), finally resulting in better capacity retention and rate performance.